This The Effect of Using Strip Story dictation on StudentsAbility in Speaking to The tenth Grade Students of SMAN 4 Kot Langsa - Fadlia Fadlia Fadlia (Journal of Education, Linguistics, Literature and Language Teaching, 2018)
This Study deals with the effect of using Strip Story Dictation on Students' ability in Speaking. The Population of this research is the students of SMA Negeri 4 Langsa. The classes X2 and X6 or 72 students are taken to be the sample randomly. The group X2 as the experimental group is taught by Strip Story Dictation, and the group X6 as the control group is taught by Conventional teaching method. In this study the instrument for collecting the data is an oral test for retelling the story through dictation. The data of speaking is analyzed by applying the t-test formula. After the data is processed and analyzed, it is found that the t-test obtained (6.207) is higher than t-table (2.000) at p=5%. It is concluded that the hypothesis is accepted. It means that teaching using Strip Story Dictation has a significant effect on Students' ability in speaking.